Interdecadal Sea Level Variations in the Pacific: Distinctions Between the Tropics and Extratropics. Issue 13 (6th July 2018) - Merrifield, M. A.; Thompson, P. R.
Abstract: Long tide gauge records from Fremantle and San Diego are used to examine interdecadal sea level fluctuations and their relationship to Pacific climate variability. The sea level difference between the tide gauges and the Southern Oscillation Index (SOI) provide a consistent depiction of trade wind variations along the equator over the past century. The sea level difference and SOI exhibit weak interdecadal variability prior to the late 1970s, followed by an extended 40‐year period of high levels at San Diego and low at Fremantle, and low SOI levels signifying weakened equatorial trade winds. By referencing the tide gauge records to global mean sea level, we infer that Pacific trade winds exhibited weak departures from mean conditions on interdecadal time scales prior to the late 1970s and that a prolonged El Niño‐like lull dominated the tropics at the end of the century. A recent shift suggests that the trades are reverting back to the El Niño‐like state. These tropical interdecadal variations have counterparts in the extratropical North Pacific after the 1970s, as captured by the Pacific Decadal Oscillation, but the early twentieth century quiescent phase in the tropical Pacific is not reflected in the extratropics, which exhibits more energetic oscillatory behavior over the same time span. Plain Language Summary: Long tide gauge records from Fremantle and San Diego provide a measure of interdecadal variations in trade wind forcing that impacts both locations. The records indicate substantial interdecadal sea level variation after the 1970s caused by a prolonged relaxation of the Pacific trade winds. Sea level and trade wind variations of this sort were considerably weaker earlier in the century. Measures of interdecadal climate variations in the extratropical North Pacific covaried with the trade winds after the 1970s, but the correspondence breaks down early in the century when tropical winds were near normal and the extratropics exhibited energetic interdecadal variability. The findings support previous studies that emphasize that the tropical and extratropical Pacific are not always in sync at these time scales, which has ramifications for understanding the underlying drivers of these variations as well as for decadal climate prediction. Key Points: Tide gauge sea level and the SOI highlight a prolonged equatorial trade wind relaxation after the 1970s Interdecadal trade wind variations were of weaker amplitude earlier in the 20th century In contrast, interdecadal climate variations in the midlatitude North Pacific are more consistent in amplitude over the century